Inhibition of Adrenergic and Non‐Adrenergic Smooth Muscle Contraction in the Human Prostate by the Phosphodiesterase 10‐Selective Inhibitor TC‐E 5005. Issue 15 (15th July 2016) - Hennenberg, Martin; Schott, Melanie; Kan, Aysenur; Keller, Patrick; Tamalunas, Alexander; Ciotkowska, Anna; Rutz, Beata; Wang, Yiming; Strittmatter, Frank; Herlemann, Annika; Yu, Qingfeng; Stief, Christian G.; et al.
Abstract : BACKGROUND: The phosphodiesterase (PDE) 5 inhibitor tadalafil is available for treatment of male lower urinary tract symptoms (LUTS), while the role of other PDE isoforms for prostate smooth muscle tone is still unknown. Here, we examined effects of the PDE10‐selective inhibitor TC‐E 5005 on smooth muscle contraction in human prostate tissue. METHODS: Prostate samples were obtained from patients undergoing radical prostatectomy. Expression of PDE10 was addressed by RT‐PCR, Western blot, and fluorescence staining with different markers. Effects of TC‐E 5005 and tadalafil on contraction, and relaxation of prostate strips were studied via organ bath. RESULTS: PDE10A was detectable by RT‐PCR, Western blot, and fluorescence staining in prostate tissues. Colocalization with markers suggested expression of PDE10A in smooth muscle cells and catecholaminergic nerves. Norepinephrine, the α1 ‐adrenergic agonist phenylephrine, the thromboxane A2 analogue U46619, and endothelins 1–3 induced concentration‐dependent contractions of prostate strips, while electric field stimulation (EFS) induced frequence‐dependent contractions. Application of TC‐E 5005 (500 nM) caused significant inhibition of norepinephrine‐, phenylephrine‐, and endothelin‐3‐induced contractions. Inhibition of EFS‐induced contractions by TC‐E 5005 ranged around 50%, resembling inhibition of EFS‐induced contractions by tadalafil (10 μM). The prostacyclin analog treprostinil and the nitric oxide donor DEA NONOate induced relaxations of precontracted prostate strips, which were significantly amplified by TCE 5005. CONCLUSIONS: The PDE10‐selective inhibitor TC‐E 5005 inhibits adrenergic and neurogenic smooth muscle contractions in the human prostate. TC‐E 5005 inhibits neurogenic contractions with similar efficacy than tadalafil, so that urodynamic effects in vivo appear possible. Prostate 76:1364–1374, 2016 . © 2016 Wiley Periodicals, Inc.